2020
DOI: 10.1212/wnl.0000000000010985
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between effort perception and poststroke fatigue

Abstract: ObjectiveTo test the hypothesis—post-stroke fatigue, a chronic, pathologic fatigue condition, is driven by altered effort perception.ParticipantsFifty-eight non-depressed, mildly impaired stroke survivors with varying severity of fatigue completed the study.Main outcome measuresSelf-reported fatigue (trait and state), perceived effort—PE (explicit and implicit) and motor performance was measured in a handgrip task. Trait fatigue was measured using Fatigue Severity Scale-7 and Neurologic Fatigue Index. State fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…This measure takes advantage of the susceptibility of visual perception to physical effort where high effort unfavourably biases distance estimation [ 62 ]. On similar lines, a line length estimation task was developed and shown to be biased by prior exertion, which we use as a measure of implicit PE [ 21 , 63 ]. We showed that trait fatigue is explained by implicit PE but not explicit PE in a physical task [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This measure takes advantage of the susceptibility of visual perception to physical effort where high effort unfavourably biases distance estimation [ 62 ]. On similar lines, a line length estimation task was developed and shown to be biased by prior exertion, which we use as a measure of implicit PE [ 21 , 63 ]. We showed that trait fatigue is explained by implicit PE but not explicit PE in a physical task [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…PE was measured in an isometric handgrip task with a hand-held dynamometer (Biometrics Ltd, Newport, UK) performed using the dominant hand [ 21 ]. Force data from the dynamometer were acquired at 500 Hz via a data acquisition interface (Power1401, CED) and recorded in MATLAB (2016b, MathWorks).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative methods of quantifying the subjective perception of effort that are not based on self-reported assessment (e.g. De Doncker et al, 2020) or paradigms used to directly assess the influence of the subjective value of effort on behaviour (e.g. Massar et al, 2018) may provide a means of further substantiating the evidenced relationship between fatigue and effort perception and its subsequent effect on performance.…”
Section: With Fatigue)mentioning
confidence: 99%
“…Perceived effort PE was measured in an isometric hand grip task with a hand-held dynamometer (Biometrics Ltd, Newport, UK) performed using the dominant hand as in De Doncker et al [21]. Measures of implicit and explicit PE were obtained using a line length estimation task and a VAS respectively.…”
Section: Stimulationmentioning
confidence: 99%